Actinomadura logoneensis sp. nov., a novel actinomycete isolated from the soil. Issue 9 (9th July 2019) - Shi, Linlin; Han, Liyuan; Guo, Xiaowei; Zhao, Junwei; Wang, Jiabin; Wang, Han; Jiang, Shanwen; Xiang, Wensheng; Wang, Xiangjing
Abstract : One novel actinobacterial isolate, designated strain NEAU-G17 T, was isolated from muddy soil collected from a riverbank in Chad and characterised using polyphasic approach. Morphological and chemotaxonomic characteristics of this strain coincided with those of the genus Actinomadura . The 16S rRNA gene sequence analysis showed that strain NEAU-G17 T was most closely related to Actinomadura oligospora JCM 10648 T (98.7 %) and Actinomadura gamaensis NEAU-Gz5 T (98.6 %). Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NEAU-G17 T formed a cluster with Actinomadura oligospora JCM 10648 T, Actinomadura gamaensis NEAU-Gz5 T and Actinomadura rupiterrae CS5-AC15 T (96.4 %). However, the combination of DNA–DNA hybridisation values and some phenotypic characteristics allowed the isolate to be differentiated from their most closely related species. The major menaquinones were identified as MK-9(H4 ), MK-9(H6 ) and MK-9(H8 ). Their polar lipid profile was found to contain diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, phosphatidylinositol mannoside, an unidentified phospholipid and an unidentified lipid. The major fatty acids were identified as C16 : 0, iso -C16 : 0 and C18 : 1 ω9c. Therefore, it is proposed that strain NEAU-G17 T should be classified as representative of a novel species of the genus Actinomadura, for which the name Actinomadura logoneensis sp. nov. is proposed. The type strains is NEAU-G17 T (=CGMCC 4.7411 T =DSM 105122 T ).